PO.7.149 Associations between abnormal bmi and patient-reported health-related quality of life before and after therapeutic intervention in patients with systemic lupus erythematosus. (27th September 2022) - Borg, A; Soltani, A; Emamikia, S; Lindblom, J; Gomez, A; Von Perner, G; Enman, Y; Heintz, E; Regardt, M; Grannas, D; Parodis, I
Abstract : Purpose: To investigate whether abnormal body mass index (BMI) is associated with patient-reported health-related quality of life (HRQoL) impairments in terms of experienced diminutions in different dimensions of the 3-level Euro Quality of Life 5-dimensions (EQ-5D-3L) questionnaire, before and after a 52 week-long therapeutic intervention for moderately to severely active systemic lupus erythematosus (SLE) within the frame of phase III clinical trials. Methods: We conducted a post-hoc analysis of data from two phase III clinical trials which evaluated the efficacy of belimumab in SLE patients, i.e. BLISS-52 (NCT00424476 ; N=865) and BLISS-76 (NCT00410384 ; N=819). Abnormal BMI was defined as underweight (BMI <18.5 kg/m2), pre-obesity (25≤ BMI <30 kg/m2), and obesity (BMI ≥30 kg/m2). HRQoL impairments were defined as experiencing problems (some/moderate; severe/extreme) in each one of the five dimensions of the descriptive system of EQ-5D-3L. Pearson's chi-square tests were used to determine potential associations between abnormal BMI and experiencing problems in EQ-5D-3L at baseline and week 52, using normal weight as the comparator. Multivariable logistic regression models were used to adjust for potential confounders, i.e. age, ethnicity, SLE disease activity, and prednisone dose. Results at week 52 were also adjusted for baseline EQ-5D-3L responses and belimumab use to capture whether BMI independently affected the post-treatment EQ-5D outcome. Results: EQ-5D-3L data were available in a total of 1655 patients. Proportions of patients reporting problems at baseline ( table 1 ) were greater among pre-obese versus normal-weighted patients, with the highest difference regarding mobility (47.1% versus 35.4%; odds ratio (OR): 1.63; 95% confidence interval (CI): 1.28–2.06; P<0.001) and pain or discomfort (PD) (83.2% versus 75.2%; OR: 1.63; 95% CI: 1.21–2.19; P=0.001). Proportions of patients reporting problems were greater among obese versus normal-weighted patients regarding all EQ-5D dimensions ( table 1 ). Post-intervention, similar results were seen for both the pre-obese patients and the obese patients, in comparison with normal-weighted patients ( table 2 ). In multivariable logistic regression analysis, obesity was associated with unfavourable HRQoL in all EQ-5D-3L dimensions at baseline (P<0.05 for all), showing the strongest association with mobility (OR: 2.09; 95% CI: 1.57–2.79; P<0.001), and pre-obesity with problems regarding mobility (OR: 1.42; 95% CI: 1.11–1.82; P=0.005). Post-intervention, obesity was associated with problems in mobility and pain/discomfort, and pre-obesity with problems in mobility and self-care (P<0.05 for all). Conclusions: Our study corroborates known associations between high BMI and HRQoL impairments. Obesity appears to negatively impact on mobility and contribute to pain despite therapy. Investigation of whether weight control can improve HRQoL in a prospective setting is warranted.